Prevalence and associated factors of psychosocial and behavioral problems in Indonesian adolescent students during the COVID-19 pandemic - Sutomo, Retno; Ramadhani, Fadhila Pratama Rizqi; Hanifa, Intan Noor (Frontiers in Pediatrics, 2022)
Background: The COVID-19 pandemic and the subsequent measures to control it, such as social distancing, school closure, and online learning, put adolescent students at higher risk of psychosocial and behavioral problems (PSBP). The adverse potential is more concerning as the outbreak continues, especially in limited-resource countries, and requires further mitigation. Objective: To assess the prevalence and factors associated with PSBP in Indonesian adolescent students in the COVID-19 pandemic Subject/Methods. We conducted a cross-sectional study in Yogyakarta Province, Indonesia, involving junior high school students. An anonymous online questionnaire in google form format was used to collect demographic data and the potential variables and screen the PSBP with the strength and difficulty questionnaire (SDQ). Logistic regression was applied to determine the independent variables. Results. Six hundred seventy-six subjects participated, including 237 males (35.1%) and 439 females (64.9%). There were 34.6% of subjects with PSBP, with a peer-relation problem as the most common one. The multivariable logistic regression showed that subjects with longer screen time duration and more family conflicts were more likely to have PSBP, with an adjusted prevalence ratio (PR) of 1.5 (95% CI: 1.1 to 2.1, p=0.025) and 2.4 (95% CI: 1.5 to 3.8, p<0.001), respectively, whereas whom with better family cohesion are less likely to have the problem with an adjusted PR of 0.4 (95% CI: 0.3 to 0.6, p<0.001). Conclusions. There is a high prevalence of PSBP among Indonesian adolescent students during the COVID-19 pandemic. Longer screen time duration and more family conflict are associated with higher prevalence, whereas better family cohesion with lower prevalence of PSBP.